Falls prevention for people with dementia: a knowledge translation intervention - Meyer, C.; Hill, Keith; Hill, S.; Dow, B. (Sage Publications Ltd., 2019)
© The Author(s) 2019. Purpose: Strong evidence exists for falls prevention, yet uptake of strategies can be fragmented and limited. For people with dementia, adoption of strategies may be impacted by changes in memory and planning. This paper describes the findings of a knowledge translation intervention for adoption of falls prevention strategies for people with dementia. Methods: Twenty-five dyads (people with dementia and their caregivers) participated in this mixed method intervention. The Knowledge to Action framework guided: collation of existing evidence into a useable format; identification of individual issues; understanding context; and evaluation of change over time. Demographic details, functional status, dementia severity, activity level, self-efficacy, falls risk and readiness to change behaviour were collected at baseline, 6 and 12 months. Goal setting and action planning using a discussion tool drove implementation. Results: Falls rates were 5.4 falls per 1000 days for the 12-month period, with no significant change in functional capacity or self-efficacy. There was a non-significant trend towards reduced falls risk. Readiness to change behaviour for falls risk increased from 84% to 96% by 6 months, with most moving from contemplation into action (n = 16), or preparation into action (n = 36), with adoption of strategies high (82%). Conclusion: Engagement with the person with dementia and their caregiver, through identification of their needs and preferences, and enabling choice resulted in high adoption of falls prevention strategies.